Forever young, Though Forever Changing: Evolution of the Vampire - Lima, Maria Antónia (2015)
The enduring influence of the vampire myth on many young people today reveals the relevance of one of the nineteenth century’s most powerful surviving archetypes. Yet, since Bela Lugosi’s portrayal of Bram Stoker’s Dracula, the figure of the vampire has undergone many transformations. In recent years, works such as Anne Rice’s Vampire Chronicles, Elizabeth Kostova’s The Historian and Stephanie Meyers’s Twilight series illustrate this evolution. This article strives to understand how pervasive the vampire tale currently is in world culture and why this may be so at this particular time, interested as we are in images of eternal youth. Besides, it aims at discussing what the vampire myth can tell us about sexuality, power, alienation, sickness, evil, loneliness and death, at the same time as it tries to establish whether vampirism may be regarded not just as a looming presence in the night, but as a symbol of our own human insecurities and desire for love, justice and freedom.